The reality of the practice of Arabic language teachers in the primary stage of reciprocal teaching from the perspective of the specialty supervisors - Khadija Najm Abdel Qader; Ramla Jabbar Kazem ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
The study aims to identify the degree of practice of Arabic language teachers in the primary stage of reciprocal teaching, from the point of view of the supervisors of the specialty. The researcher followed the descriptive approach, and the sample consisted of (77) male and female supervisors for the academic year (2023/2024). The researcher prepared one tool to achieve the objectives of her research. After verifying the validity and reliability procedures, the tool became composed of (50) paragraphs. To process the data statistically, the researcher used percentages, Chi-square, Pearson's correlation coefficient, Cronbach's alpha equation, split-half, Spearman-Brown equation, weighted means, standard deviations, and percentage weights. The results showed that the general performance of Arabic language teachers of reciprocal teaching strategies came at a level sometimes, with the exception of some paragraphs that came at a level always.